Students perceptions of mathematics classroom environment, mathematics efficacy, and mathematics achievement : A study in Keningau, Sabah, Malaysia - Murugan a/l Rajoo (2011)
Mathematics classroom environment, mathematics efficacy and mathematics achievement are some of the important mathematical constructs in teaching and learning of Mathematics in the classroom. This study compared such constructs between rural and urban schools in Keningau, Sabah as well as between genders. This study also focused on determining the relationship between these three constructs. Two urban and two rural secondary schools with sample sizes of 235 and 210 each and total sample size of 445 were selected to participate in this study. Three research instruments were used in this study. A 76-item mathematics classroom environment questionnaire based on "What is Happening in This Classroom" (WIHIS) and the Constructivist Learning Environment Survey (CLES) were used to determine the mathematics classroom environment. Another questionnaire to determine mathematics efficacy with 10 items adapted from PISA (2004) was also used. The students' mathematics achievement was determined using a test comprising of 20 multiple choice questions and 5 subjective questions based on the first five chapters in Mathematics Form 4 syllabus. Data from the study was analyzed with SPSS 17 .0 using both descriptive and inferential statistical analyses. Findings showed the students had a moderate perception of their mathematics classroom environment and mathematics efficacy. Mathematics achievement was low, with female students achieving better than males in their mathematics assessment while urban students did better than rural students. There was no significant difference in perception of mathematic learning environment based on school location and gender. However, differences in perception of mathematics efficacy were insignificant based on school location but significant for gender with female has better mathematics efficacy compared to male. Significant of weak correlations were found between mathematics classroom learning environment, mathematics efficacy and mathematics achievement. The research findings bring some meaningful implications to the teaching and learning of mathematics at urban and rural secondary school as well as the training of mathematics teachers in Malaysia.